أهمية تدنيه التكاليف بتطبيق محاسبة التحليلية - عيساوي, مريم (My University, 2020)
In light of recent and rapid progress in the business environment, Algerian economic institutions need to quickly adapt to external changes in the surrounding environment, and the necessity to keep pace with the economic transformations that take place, and not to ignore the reactions of their competitors, and this is what requires them to develop methods and strategies to support their competitiveness and think about how Maintaining its position in the market as long as possible. In order for the institution to achieve these goals, it must improve the best use of its available resources and work to control its various costs and find ways to minimize it, because costs are no longer just a way to measure the actual expenditures that have taken place within the organization, but their depreciation has become an important process in Reducing product prices. To achieve this transition, it is necessary to adopt methods and methods that depend on coding the choices that are adopted by these institutions into productive work and making their performance better than their competitors. Among what can be addressed in this regard is the need to search for the methods necessary to minimize costs, even though this will not be achieved until there is a serious and continuous work. The cost accounting system is a necessary means for arranging and organizing financial, economic and legal information that affects the financial liability of the individual and The institution, which is also one of the techniques that economic development was a major reason for its emergence in assisting the management and determining the costs and studying them . The aim of our study was to attempt to apply the importance of unit cost estimation and the role of cost accounting as an information system in the hydrocarbon sector
دراسة على شركة سونطراك ارزيو